Phase-field modeling of geologic fractures - Choo, Jinhyun (Frontiers in Built Environment, 2024)
Geologic fractures such as joints, faults, and slip surfaces govern the stability and performance of many subsurface systems in the built environment. As such, a variety of approaches have been developed for computational modeling of geologic fractures. Yet none of them lends itself to a straightforward utilization with the classical finite element method widely used in practice. Over the past decade, phase-field modeling has become a popular approach for simulating fracture, because it can be implemented simply with the standard finite element method without any surface-tracking algorithms. However, the standard phase-field formulations do not incorporate several critical features of geologic fractures, including frictional contact, pressure-dependence, quasi-brittleness, mode-mixity, and their combined impacts on cracking. This article provides a brief report of a novel phase-field model that incorporates these features of geologic fractures in a well-verified and validated manner. Remarkably, the phase-field model allows one to simulate the combination of cohesive tensile fracture and frictional shear fracture without any algorithms for surface tracking and contact constraints. It is also demonstrated how phase-field modeling enables us to gain insights into geologic fractures that are challenging to investigate experimentally.